Heterosis and hybrid rice breeding - Virmani, Sant S. (Springer-Verlag, 1994)
A concise account of hybrid breeding in rice, a newly deployed breeding approach to increase the yield, is provided. Research on heterosis, male sterility systems, outcrossing mechanisms, disease and insect resistance and grain quality considerations in hybrid rice are reviewed. The current status and further outlook of hybrid rice breeding in different countries are discussed. Since the levels of hybrid rice research in and outside China differ, these are discussed separately